Zeros of Cubic Functions
Zeros of Cubic Functions
Zeros of Cubic Functions
PORTFOLIO
ZEROS OF CUBIC
FUNCTIONS
Peter Hamilton
Zeros of cubic functions
HL Type I Investigation
In order to find the tangent at any given point on the graph, the slope
at that point must be found. To find the slope at any given point, the
first differential of the function can be used:
To find the tangent line of the average of two of the three roots, the
value must be plugged into the first differential equation in order to
find its slope.
y=m xb
By using the values obtained for the slope of these tangent lines, the
next values necessary are the respective y values in each case. These
can be determined by plugging the averages into the original
equation.
y=mx+b
y=mxb
y=−7.59375 m=−10.125 x=−0.75
−7.59375=−10.125 −0.75b
b=−15.1875
y=−10.125 x−15.1875
y=mxb
y=4.21875 m=−1.125 x=−2.25
4.21875=−1.125−2.25b
b=1.6875
y=−1.125 x1.6875
y=mxb
y=−13.5 m=−4.5 x=0
−13.5=−4.50b
b=−13.5
y=−4.5 x−13.5
y=−10.125 x−15.1875
Let y=0
0=−10.125 x−15.1875
15.1875=−10.125 x
x=−1.5
y=−4.5 x−13.5
Let y=0
0=−4.5 x−13.5
13.5=−4.5 x
x=−3
In each given scenario, the line tangent to the average of two roots of
a cubic equation also passes through the third root. To further
demonstrate this conjecture, similar cubic functions can be taken and
the same result may be found.
example 1
f x=x 3 −2 x 2−5 x6
Roots at: x=−2 x=1 x=3
Roots -2 and 3
−23
Average value: =0.5
2
3 2
f 0.5=0.5 −20.5 −50.56=3.125
f 1 x=3 x 2−4 x−5
f 1 0.5=30.52−40.5−5=−6.25
y=mxb
3.125=−6.250.5b
b=6.25
y=−6.25 x6.25
Let y=0
0=−6.25 x6.25
x=1
Roots 1 and 3
13
Average value: =2
2
3 2
f 2=2 −22 −526=−4
f 1 x=3 x 2−4 x−5
1 2
f 2=32 −42−5=−1
y=mxb
−4=−12b
b=−2
y=−x±2
Let y=0
0=−x−2
x=−2
Roots -2 and 1
−21
Average value: =−0.5
2
f −0.5=−0.53−2−0.52−5−0.56=7.875
1 2
f x =3 x −4 x−5
f 1 −0.5=3−0.52−4−0.5−5=−2.25
y=mxb
7.875=−2.25−0.5b
b=6.75
y=−2.25 x6.75
x=3
Let y=0
0=−6.25 x6.25
x=1
Demonstrated graphically:
Example 2
3 2
f x=x −3 x −4 x12
Roots at: x=−2 x=2 x=3
Roots -2 and 2
−22
Average value: =0
2
3 2
f 0=0 −30 −4012=12
1 2
f x=3 x −6 x−4
f 1 0=302−60−4=−4
y=mxb
12=−40b
b=12
y=−4 x12
Let y=0
0=−4 x12
x=−3
Roots -2 and 3
−23
Average value: =0.5
2
3 2
f 0.5=0.5 −30.5 −40.512=9.375
f 1 x=3 x 2−6 x−4
f 1 0.5=30.52−60.5−4=−6.25
y=mxb
9.375=−6.250.5b
b=12.5
y=−6.25 x12.5
Let y=0
0=−6.25 x12.5
x=−2
Roots 2 and 3
23
Average value: =2.5
2
3 2
f 2.5=2.5 −32.5 −42.512=−1.125
f 1 x=3 x 2−6 x−4
1 2
f 2.5=32.5 −62.5−4=−0.25
y=mxb
−1.125=−0.252.5b
b=−0.5
y=−0.25 x−0.5
Let y=0
0=−0.25 x−0.5
x=−2
Demonstrated graphically:
These examples are consistent with the idea that the tangent to the
average of any two roots of a cubic passes through the third root. In
order to prove this as a property for all roots, a general case must be
taken and proven true for all instances.
A function with roots , , and can be used to provide a general
case.
f x=x−x−x−
=x 2− x− x x−
= x 3− x 2− x 2 x− x 2 x x−
f x=x 3− x 2 x−
By substituting the value into the first differential we can find
2
the slope of the average of two roots of a cubic.
This value, along with that obtained with the first differential can be
used to find the tangent to the average of two roots. By substituting
the corresponding slope and y-value, the tangent can be solved for.
y=mxb
−3 2 2−32 2 −4 2 2
Let y=
8
2
−−
m=
4
x=
2
− 2−32 2 −4 2 2 −−2
3 2
= b
8 4 2
−32 2−32 2 −4 2 2 3− 2−2 3
b=
8
2 2
2 −4 2
b=
8
2 2 2
−− 2 −4 2
y= x
4 8
With the tangent line completed, the test to the conjecture can be
shown by substituting the root , 0 into equation. If the equation
holds true, then the conjecture has been proven for all cubics.
−−2 2 2 −4 2 2
y= x
4 8
Let y=0 x=
−−2 2 2 −4 2 2
0=
4 8
2 2
2 −4 2 2
2
−2
0=−2
8 8
2 2 2 2
−2 4 −2 2 −4 2
0=
8
0
0= =0
8
Therefore this conjecture has been proved true for all cubic functions
which can be expressed as x−x−x− .
There exist certain cubic functions which contain roots unlike the
previous examples. Some cubics only have one root, others have only
two roots, and others have one real root and two imaginary ones.
f x=x 3 x 2 −8 x−12
Roots x=3 x=−2 with a double root at x=−2
Roots 3 and -2
3±2
Average =0.5
2
f 0.5=0.530.52−80.5−12=−15.625
f 1 x=3 x 22 x−8
1 2
f 0.5=30.5 20.5−8=−6.25
y=mxb
Let y=−15.625 x=0.5 m =−6.25
−15.625=−6.25.5b
b =−12.5
Therefore the tangent equation is: y=−6.25 x−12.5
By substiting the x and y values of the third root of the cubic, the conjecture can be tested
Let y=0 x=−2
0=−6.25−2−12.5=0
Proven True
Roots -2 and -2
−2±2
Average =−2
2
3 2
f −2=−2 −2 −8−2−12=0
f 1 x=3 x 22 x−8
f 1 −2=3−222−2−8=0
y=mxb
Let y=0 x=−2 m =0
0=0 −2b
b =0
Therefore the tangent equation is: y=0
By substiting the x and y values of the third root of the cubic, the conjecture can be tested
Let y=0 x=3
0=0−2−0=0
Proven True
Two Roots Shown Graphically
Thus, it has been shown that for cubics with either a double or triple
root follows the conjecture stated above. The final area of
investigation is beyond the domain of real numbers. A cubic with one
real and two complex roots will also adhere to the conjecture, as is
shown in the following example:
f x= x 3− x 2 x−1
Roots x=i x=−i x=1
Roots i and 1
1i
Average:
2
1i 1i 3 1i 2 1i
f = − −1
2 2 2 2
13 i −3−i 12 i −1 1i 2
= − −
8 4 2 2
13 i −3−i −2−4 i 244 i −8
=
8
1i −62 i
f =
2 8
1 2
f x=3 x −2 x1
1i 1i 2 1i
f 1 =3 −2 1
2 2 2
1i 2 i 1i 4
f 1 =3 −4
2 4 4 4
1 1i 2 i
f =
2 4
Using the value of slope and the x and y values of the average of the
two roots, the tangent line can be solved for:
y=mxb
−62 i 1i 2 i
Let y= x= m=
8 2 4
−62 i 2 i 1i
= b
8 4 2
−4
b =
8
2 i −4
y= x
4 8
If the third root is subsituted the equation should still be true, proving the conjecture
Let y=0 x=−i
2 i −4
0= −i
4 8
4 −4
0=
8 8
4−4
0= =0
8
Proven True
Roots −i and 1
1−i
Average:
2
3 2
1−i 1−i 1−i 1−i
f = − −1
2 2 2 2
1−3 i −3i 1−2 i −1 1−i 2
= − −
8 4 2 2
1−3 i −3i −24 i 24−4 i −8
=
8
1−i −6−2 i
f =
2 8
1 2
f x=3 x −2 x1
2
1 1−i 1−i 1−i
f =3 −2 1
2 2 2
1−i −2 i 1−i 4
f 1 =3 −4
2 4 4 4
1 1−i −6 i −44 i 4 −i
f = =
2 2 2
Using the value of slope and the x and y values of the average of the
two roots, the tangent line can be solved for.
y=mxb
−3−i 1−i −i
Let y= x= m=
4 2 2
−3−i −i 1−i
= b
4 2 2
−3−i i 1 −1
b = =
4 2
−i 1
y= x−
2 2
If the third root is subsituted the equation should still be true, proving the conjecture
Let y=0 x=i
−i 1
0= i −
2 2
1 1
0= −
2 2
1−1
0= =0
2
Proven True
Roots −i and i
i −i
Average: =0
2
f 0=03−0 20−1=−1
f 1 x=3 x 2 −2 x1
f 1 0=302 −201
f 1 0=30−401=1
y=mxb
Let y=−1 x=0 m =1
−1=10b
b =−1
y= x−1
If the third root is subsituted, the equation should still be true, proving the conjecture
Let y=0 x=1
0=1−1=0
Proven True
Graph and real tangents shown graphically
In conclusion, it is evident that this conjuncture has proved true.
For a cubic in form f x= x− x− x− the tangent at the
average of any two roots will pass through the third root.
It has been shown true for various cubics, been demonstrated true for
a general case, and verified with examples including one root, two
roots, and one real and two complex roots.